2021
DOI: 10.3390/su13010353
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Wind and Sea Ice in Driving the Deglacial Change in the Southern Ocean Upwelling: A Modeling Study

Abstract: The Southern Ocean (SO) played a fundamental role in the deglacial climate system by exchanging carbon-rich deep ocean water with the surface. The contribution of the SO’s physical mechanisms toward improving our understanding of SO upwelling’s dynamical changes is developing. Here, we investigated the simulated transient SO atmosphere, ocean, and sea ice evolution during the last deglaciation in a fully coupled Earth system model. Our results showed that decreases in SO upwelling followed the weakening of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 98 publications
(175 reference statements)
0
6
0
Order By: Relevance
“…For example, the TraCE-21ka model replicated the Asian-African monsoon [88], El Niño [89], the highlatitude seasonal temperature [90], the AMOC transport, and the SH regional sea surface temperature [5]. In addition, the model reasonably simulated the present-day atmospheric circulation and sea surface temperature in the SO [49,91].…”
Section: Model Performancementioning
confidence: 83%
“…For example, the TraCE-21ka model replicated the Asian-African monsoon [88], El Niño [89], the highlatitude seasonal temperature [90], the AMOC transport, and the SH regional sea surface temperature [5]. In addition, the model reasonably simulated the present-day atmospheric circulation and sea surface temperature in the SO [49,91].…”
Section: Model Performancementioning
confidence: 83%
“…Previous studies have shown that the melting of Antarctic sea ice releases freshwater, which increases the buoyancy of Southern Ocean upwelled water (Iudicone et al, 2008) and strengthened the upper limb of the ocean meridional overturning circulation (Abernathey et al, 2016;Saenko et al, 2002). Furthermore, numerical simulations have confirmed the importance of freshwater fluxes in determining changes in Southern Ocean upwelling during the last deglacial period (Mandal et al, 2021;Mandal et al, 2022;Morrison et al, 2011).…”
Section: Introductionmentioning
confidence: 82%
“…The paleoclimatology community recognizes that the Southern Ocean overturning circulation is primarily driven by wind (Anderson et al, 2009;Menviel et al, 2018). Several studies, however, have found that changes in buoyancy flux caused by freshwater discharge (Abernathey et al, 2016;Liu et al, 2021), ocean eddies (Lauderdale et al, 2017), topography (Liu et al, 2021), and Antarctic sea ice feedback (Ferrari et al, 2014;Jansen & Nadeau, 2016;Mandal et al, 2021;Mandal et al, 2022;Marzocchi & Jansen, 2017;Stein et al, 2020) contribute to the Southern Ocean dynamical changes during the most recent deglacial period. As a result, it is critical to comprehend the role of Antarctic sea ice in surface buoyancy flux, which influences the Southern Ocean overturning circulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively stable LGM atmospheric CO 2 levels suggest that this was likely not a significant source of CO 2 to the atmosphere at this time. Model simulations have projected that reduced deep ocean ventilation was linked to expanded sea ice along with equatorward shifted Westerlies and Southern Ocean fronts in the LGM (Chen & Wang, 2021; Ferrari et al., 2014; Mandal et al., 2021; Menviel et al., 2015; Russell et al., 2006; Toggweiler et al., 2006). These new data are the first to clarify that the individual fronts did not move in sync or in parallel and identifies that the narrowing of the SAZ in the Indian Ocean was a significant process sequestering CO 2 .…”
Section: Lgmmentioning
confidence: 99%